Partial Purification and Characterization of Rhodanese from Rainbow Trout (Oncorhynchus mykiss) Liver - Hossein Tayefi-Nasrabadi; Reza Rahmani (The Scientific World Journal, 2012)
Cyanide is one of the most toxic substances present in a wide variety of food materials that are consumed by animals. Rhodanese, a ubiquitous enzyme, can catalyse the detoxification of cyanide by sulphuration reaction. In this study, rhodanese was partially purified and characterized from the liver tissue homogenate of the rainbow trout. The enzyme was active in a broad range of pH, from 5 to 12. The optimal activity was found at a high pH (pH 10.5), and the temperature optimum was 25∘C. The enzyme was heat labile, losing > 50% of relative activity after only 5 min of incubation at 40∘C. The Km values for KCN and Na2S2O3 as substrates were 36.81 mM and 19.84 mM, respectively. Studies on the enzyme with a number of cations showed that the activity of the enzyme was not affected by Sn2+, but Hg2+, Ba2+, Pb2+, and Ca2+ inhibited and Cu2+ activated the enzyme with a concentration-dependent manner.